Standardized school-leaving exam in mathematics: manifold effects on teaching, teacher cooperation and satisfaction - Ableitinger, Christoph; Gruber, Johanna (Frontiers in Education, 2024)
The recent implementation of a standardized school-leaving exam (SSLE) in Austria enables research on the effects of this educational policy decision on mathematics teaching (use of tasks and digital tools) and on mathematics teachers (attitudes, cooperation, satisfaction and self-concept). An interview study with ten teachers, each of whom prepared students several times for the traditional, individually designed as well as for the new, standardized school-leaving exam, reveals a multifaceted picture. In particular, it shows that the SSLE as a steering instrument has great influence on the use of tasks in the classroom and has been able to advance the digitization of mathematics teaching within a short period of time. Cooperation among the teachers in the respective schools has clearly increased as a result of the SSLE, even though this is not perceived as unreservedly positive. Interestingly, the interviews did not reveal any evidence of harmful competition between teachers in a school regarding the performance of their students in the SSLE. While the study shows that teachers are basically positive about reforms and are willing to implement them, they also want changes to be well prepared, argued and communicated in time.